2011
DOI: 10.1098/rsbl.2010.1164
|View full text |Cite
|
Sign up to set email alerts
|

Peptide transport and animal growth: the fish paradigm

Abstract: Physiology Opinion piecePeptide transport and animal growth: the fish paradigm Protein digestion products are transported from the intestinal lumen into the enterocyte both in the form of free amino acids (AAs), by a large variety of brush border membrane AA transporters, and in the form of di/tripeptides, by a single brush border membrane transporter known as PEPtide Transporter 1 (PEPT1). Recent data indicate that, at least in teleost fish, PEPT1 plays a significant role in animal growth by operating, at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 35 publications
1
43
0
1
Order By: Relevance
“…Studies in several teleost species have revealed that intestinal expression levels of PepT1 respond to fasting and refeeding, with expression levels rising in some species after short-term fasting, followed by a decline in long-term fasting/starvation. Re-feeding stimulates upregulation of PepT1 above pre-fasted levels, indicating sensitive responsiveness to food availability and a potential role for the transporter in the phenomenon known as compensatory growth [51][54]. Aquaculture researchers are keenly interested in use of PepT1 as an indicator of protein uptake and as a direct predictor of animal growth [51], [55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in several teleost species have revealed that intestinal expression levels of PepT1 respond to fasting and refeeding, with expression levels rising in some species after short-term fasting, followed by a decline in long-term fasting/starvation. Re-feeding stimulates upregulation of PepT1 above pre-fasted levels, indicating sensitive responsiveness to food availability and a potential role for the transporter in the phenomenon known as compensatory growth [51][54]. Aquaculture researchers are keenly interested in use of PepT1 as an indicator of protein uptake and as a direct predictor of animal growth [51], [55].…”
Section: Discussionmentioning
confidence: 99%
“…Re-feeding stimulates upregulation of PepT1 above pre-fasted levels, indicating sensitive responsiveness to food availability and a potential role for the transporter in the phenomenon known as compensatory growth [51][54]. Aquaculture researchers are keenly interested in use of PepT1 as an indicator of protein uptake and as a direct predictor of animal growth [51], [55]. PepT1 may also serve as another bridge between nutritional and immune regulation, given its roles in binding bacterial peptides and stimulation of gut innate immune activation and inflammation [56].…”
Section: Discussionmentioning
confidence: 99%
“…gradient on an abundant high-capacity, low-specificity peptide transporter (PepT1) or through endocytosis. Intestinal peptide transport is of major nutritional significance in that the intraluminal products of protein digestion are predominantly di-and tripeptides (up to 85% of the digesta in mammals) and not AA as previously believed (Taylor et al 2011;Verri et al 2011). In addition, many AA are more rapidly and efficiently absorbed in peptide form (for a review see Gilbert et al 2008).…”
Section: Nutritional Stress Response and Intestinal Oligopeptide Tranmentioning
confidence: 95%
“…(asterisk) indicates significantly different means from controls, for each time point tested (P \ 0.05). This figure has been adapted from Terova et al (2009) addition, PepT1 gene expression is up-regulated with refeeding and correlates with fish compensatory growth (Verri et al 2011). Moreover, Bakke et al (2010) have shown that dietary protein hydrolysates and free AA affect the expression of PepT1 along the digestive tract of Atlantic cod (Gadus morhua), indicating an adaptive response to keep a maximal efficiency of protein absorption at the intestinal level.…”
Section: Nutritional Stress Response and Intestinal Oligopeptide Tranmentioning
confidence: 98%
“…; Verri et al . , ). Peptide absorption has also aroused the interest of scientists working on the larval and juvenile stages of fish (see e.g.…”
Section: Digestive Physiologymentioning
confidence: 99%